KEUNGGULAN MEDIASI SEBAGAI PENYELESAIAN SENGKETA PERDATA DI SITUASI PANDEMI COVID -19 - Dikky Ramana Putra (Universitas Muhammadiyah Mataram, 2021)
The problem studied in this study is the superiority of mediation as a dispute resolution process within the scope of civil law in terms of the situation of the covid-19 pandemic outbreak. Writing this scientific journal aims to provide an understanding of how mediation is superior as a form of settlement of civil disputes in the era of the covid-19 pandemic. The COVID-19 pandemic has had an impact on the world, including the judicial process, in this case mediation in civil law. The research in this paper uses a normative legal study research method, namely library law research. Furthermore, the research data were analyzed with a descriptive analytical research approach. The approach taken to the problem refers to the side of legislation and is linked to literature or scientific works as well as doctrine (expert opinion). From the results of the research and discussion, two research findings have been found, namely, the first mediation procedure regulated in Perma RI No. 1 of 2016, carried out through three stages, the first stage is pre-mediation, the second stage is the application of mediation and the third stage is mediation implementation. Then the second thing is that it is known that the state of the covid-19 pandemic has made mediation held by teleconference, which has been regulated by Perma No. 1 of 2016 concerning the mediation process via teleconference. In resolving disputes using mediation during the outbreak of the COVID-19 outbreak, it has many advantages, namely low cost, fast process, can minimize physical meetings, and can be done using teleconference media. However, it is hoped that the Supreme Court must continue to improve the rules regarding the online mediation process to ensure the comfort and security of the parties, so that confidentiality can be guaranteed.Keywords: dispute resolution, mediation, covid-19 ABSTRAKPermasalahan yang dikaji dalam penelitian ini yaitu keunggulan mediasi sebagai proses penyelesaian sengketa di dalam ruang lingkup hukum perdata ditinjau dari situasi wabah pandemi covid-19. Penulisan jurnal ilmiah ini bertujuan untuk memberikan pemahaman mengenai bagaimana keunggulan mediasi sebagai salah satu bentuk penyelesaian sengketa perdata di era pandemic covid-19. Wabah pandemi covid-19 telah memberikan dampak terhadap dunia tak terkecuali kepada proses peradilan, dalam hal ini adalah mediasi di dalam hukum perdata. Penelitian dalam penulisan ini menggunakan metode penelitian kajian hukum normatif yaitu penelitian hukum kepustakaan. Selanjutnya data penelitian dianalisis dengan pendekatan Penelitian bersifat deskriptif analitis. Pendekatan dilakukan terhadap masalah mengacu dari sisi Perundang-undangan dan dihubungkan dengan literatur atau karya ilmiah serta doktrin (pendapat ahli). Dari hasil penelitian dan pembahasan telah ditemukan dua temuan penelitian yaitu, pertama prosedur mediasi yang diatur dalam Perma RI Nomor 1 Tahun 2016, dilaksanakan melalui tiga tahapan, tahap pertama pra mediasi, tahap kedua penerapan mediasi dan tahap ketiga implementasi mediasi. Lalu yang kedua diketahui bahwa keadaan pandemi covid-19 ini telah membuat mediasi diselenggarakan secara teleconference yang dimana hal itu telah diatur oleh perma nomor 1 tahun 2016 tentang proses mediasi melalui teleconference. Dalam menyelesaikan sengketa menggunakan mediasi di saat merebaknya wabah covid-19 memiliki banyak keunggulan yaitu berbiaya murah, proses cepat, dapat meminimalisir pertemuan fisik, dan bisa dilakukan dengan media teleconference. Namun di harapkan mahkamah agung harus terus menyempurnakan aturan mengenai proses mediasi secara online demi terjaminnya kenyamaan dan keamanan para pihak, sehingga kerahasiaannya dapat terjamin.